Low cost water permeability apparatus for concrete - Madlangbayan, Marish S.
Data on long-term behavior of concrete exposed to local environment is an important pre-requisite for performance-based of concrete structures. However, the locus of past studies is on concrete strength. Durability-related studies considering local environment in the Philippines is scarce. Since water permeability may be taken as an indicator of concrete durability, this study attempted to develop a simple and low cost water permeability apparatus based on Darcy's equation with only gravity as the driving force. The apparatus was tested for repeatability of results both for single and multi-operator cases. Usage was then demonstrated to determine the permeability of ordinary concrete, concrete with fly ash, and concrete subjected to various levels of chemical degradation. Results obtained are of the same magnitude as published data and these can be used as baseline data for future durability-related studies in the local scene.